Circulating miRNAs, Small but Promising Biomarkers for Autism Spectrum Disorder - Salloum-Asfar, Salam; Satheesh, Noothan J.; Abdulla, Sara A. (Frontiers in Molecular Neuroscience, 2019)
Autism spectrum disorder (ASD) refers to a heterogeneous group of complex neurodevelopmental disorders characterized by social skill and communication deficits, along with stereotyped repetitive behavior. miRNAs, small noncoding RNAs that have been recognized as critical regulators of gene expression, play a key role in the neurodevelopmental transcriptional networks of the human brain. Previous investigations have proven that circulating miRNAs open up new possibilities for the emerging roles of diagnostic and prognostic biomarkers in human disorders and diseases. Biomarker development has been progressively becoming more recognized as a cornerstone in medical diagnosis, paving the way to drug discoveries and limiting the progression of various diseases. Due to the complexity of ASD, considerable endeavors have either unsuccessfully identified biomarkers for the disorder or have not yet been established. Cell-free circulating miRNAs in biofluids are extraordinarily stable and considered to represent the next-generation of clinical, noninvasive, biomarkers for many pathologies including neurological and neurodevelopmental disorders. Here, we conducted a review of all peer-reviewed articles addressing the circulating profiles of miRNAs, mostly performed in serum and saliva samples in individuals with ASD.